Legal Innovations in the Sharia Fiscal System in Aceh: Towards the Integration of Zakat and Taxation - Fuadi, Fuadi; Rachmad, Andi; Ulya, Zaki (Locus: Jurnal Konsep Ilmu Hukum, 2025)
This article examines the potential for integrating zakat and taxation within Aceh's unique Sharia fiscal system. With Aceh's special autonomy and the application of Sharia law, there is a significant opportunity to harmonize zakat (Islamic almsgiving) and taxes as part of a more inclusive, equitable fiscal system. This integration is seen as a potential solution to address fiscal challenges, reduce reliance on central government transfers, and promote local economic independence. The paper explores the legal and institutional frameworks that govern zakat collection and tax policies in Aceh, identifying key opportunities for synergy between the two systems. Additionally, it discusses the challenges of reconciling national tax laws with regional Sharia regulations, the administrative hurdles of coordinating zakat data with tax authorities, and the potential for creating incentives for taxpayers to contribute zakat. The article concludes by proposing a framework for implementing a more integrated system that enhances the fiscal self-sufficiency of Aceh, supports social justice, and aligns with Islamic principles of wealth distribution. This study provides valuable insights into how regional autonomy and Sharia law can be leveraged to create a more holistic and sustainable fiscal policy in Aceh.